2020
DOI: 10.1038/s41380-020-00868-3
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin transporter availability in adults with autism—a positron emission tomography study

Abstract: Impairments in social interaction and communication, in combination with restricted, repetitive behaviors and interests, define the neurodevelopmental diagnosis of autism spectrum disorder (ASD). The biological underpinnings of ASD are not well known, but the hypothesis of serotonin (5-HT) involvement in the neurodevelopment of ASD is one of the longest standing. Reuptake through the 5-HT transporter (5-HTT) is the main pathway decreasing extracellular 5-HT in the brain and a marker for the 5-HT system, but in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 90 publications
1
29
0
Order By: Relevance
“…Similar findings have been reported in adults with ASD. Serotonin availability is significantly lower in the CNS of adults with ASD compared with controls (Andersson et al 2020). The findings of this study and many others endorse a significant association of serotonin with ASD.…”
Section: The Serotonin Pathwaysupporting
confidence: 56%
“…Similar findings have been reported in adults with ASD. Serotonin availability is significantly lower in the CNS of adults with ASD compared with controls (Andersson et al 2020). The findings of this study and many others endorse a significant association of serotonin with ASD.…”
Section: The Serotonin Pathwaysupporting
confidence: 56%
“…This gene encodes a serotonin transporter, involved in serotonergic neurotransmission. Several studies have found an association between 5HTT and ASD, with people of the spectrum exhibiting increased levels of serotonin as a result of lower 5-HTT availability in several brain areas, although the mechanism probably involves other genes interacting with 5-HTT (Coutinho et al, 2004;Veenstra-VanderWeele et al 2012;Andersson et al, 2021). Reif and colleagues (2007) also found a significant correlation between a specific allele on 5HTT and the relationship between maltreatment, stress, and adversity in childhood and violent/aggressive behavior later in life, suggesting that this gene has an impact as well on how childhood maltreatment affects adults.…”
Section: Geneticsmentioning
confidence: 99%
“…SSRIs prevent the reuptake of 5-HT by inhibiting the SERT at the presynaptic axon terminal. SERT binding is lower throughout the autistic brain, resulting in deficits in social cognition (SERT reduction in anterior and posterior cingulate cortices) and repetitive and obsessive behaviours (SERT reduction in the thalamus) (Andersson et al, 2020;Nakamura et al, 2010). Further, Makkonen et al (2008) found reduced SERT binding in the medial frontal cortex, an area connected to the ability to interpret another's thoughts and intentions (theory of mind) in children and adolescents with ASD.…”
Section: Neurotransmittersmentioning
confidence: 99%